Classdojo: A Modern Solution For Learning Grammar - Rizka Widya Sari; Yepi Sedya Purwananti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
ClassDojo is one of the form of virtual classroom that can be used to monitor every student’s behaviour during learning sessions. The purpose of this study is to examine the effectiveness of using ClassDojo is supporting students’ basic grammar. This research follows a development research using ADDIE design. The poppulation in this study consist of grammar students at Bahasaku Inggris course. The primary issues addresed in this research is students boredom in grammar class. Data were collected throgh test questionares. Data analyss technique included descriptive and stasistical analysis. Descriptive data analysis covered the feasibility of learning and achivement of indicators. Inferential data analysis included pre requisite tests such as normality test and t-test using SPSS 26.0. The Kolmogorov-Smirnov test result shows a value of 0.101 for the Pre-Test and 0.054 for the Post-Test. The Shapiro-Wilk significance value is 0.056 for the Pre-Test and 0.038 for the Post-Test. These datas show that the distribution is normal. The research findings indicate that implementing the ClassDojo application as a learning tool has a significant impact on students